Efficiency of tuned liquid dampers in mitigating vibration of a plan-irregular structure - Teh, Kun Jie (2019)
Many researches showed that one of the major causes of buildings collapse and damage might directly or indirectly due to irregular structural configuration. The buildings with regular geometry and uniformly distributed mass and stiffness in plan were suffered much less damage compared to irregular configurations. Tuned liquid dampers (TLDs) have been proposed in the past studies that were used to control the dynamic response of regular structures. In this study, the effect of the mass ratio of a rectangular TLD for suppressing dynamic responses of a plan-irregular structure was determined. The performance in term of displacement and acceleration responses when subjected to the base harmonic excitation was obtained experimentally. The structure is subjected to the free vibration and harmonic forced vibration tests with and without the presence of TLDs. The effects of the structure-TLD system with a mass ratio of 1% to 5% and bare structure system in varied plan distribution of mass were measured and investigated. This distance between the centroid and the mass for the plan-irregular condition will be 0.15m and 0.3m. In short, the damping ability was achieved with a higher mass ratio. The eccentricity did not strongly affect the damping ability of the plan-irregular structure. The dynamic responses were reduced by increasing the mass ratio of structure-TLD systems at resonance in regular structure while it is not performed similarly in plan-irregular structure. However, a mass ratio of 5% was still found to be the optimum system for peak acceleration responses control whereas a mass ratio of 5% was found to be a vital reduction of displacement responses only at the resonance frequency of 1.2Hz and above.